Vibration Response and Power Flow Characteristics of a Flexible Manipulator with a Moving Base. (15th January 2015) - Liu, Yufei; Li, Wei; Yang, Xuefeng; Fan, Mengbao; Wang, Yuqiao; Lu, En
Abstract : Flexible manipulator generally can be modeled as a coupling system with a flexible beam and a rigid moving base. This paper investigates the vibration responses and power flow of a flexible manipulator with a moving base (FMMB). Considering the motion characteristics of the rigid base, the moving base is modeled to have a motion with disturbances, and the dynamic model of the FMMB is established. With the dynamic model, vibration responses of the FMMB for the rigid base having disturbance velocities and accelerations are specifically presented. Subsequently, to investigate the effect of the disturbances on the vibration energy distributions of the FMMB, power flow of the FMMB is exhibited. To verify the dynamic model, an ADAMS physical model of the FMMB is constructed. It reveals that the motion characteristics of the rigid base have a noticeable effect on the vibration responses and power flow of the FMMB and should be considered. The results are significant and contribute to the vibration control of flexible manipulators.